CircRNAs Are Involved in the Rice-Magnaporthe oryzae Interaction. Issue 1 (18th October 2019) - Fan, Jing; Quan, Weili; Li, Guo-Bang; Hu, Xiao-Hong; Wang, Qi; Wang, He; Li, Xu-Pu; Luo, Xiaotian; Feng, Qin; Hu, Zi-Jin; Feng, Hui; Pu, Mei; et al.
Abstract : Rice circRNAs regulate rice immunity against the blast fungus Magnaporthe oryzae. Abstract: Circular RNAs (circRNAs) play roles in various biological processes, but their functions in the rice ( Oryza sativa ) response to Magnaporthe oryzae remain elusive. Here, we demonstrate that circRNAs are involved in the rice- M. oryzae interaction using comparative circRNA-sequencing and transgenic approaches. We identified 2932 high-confidence circRNAs from young leaves of the blast-resistant accession International Rice Blast Line Pyricularia-Kanto51-m-Tsuyuake (IR25) and the blast-susceptible accession Lijiangxin Tuan Heigu (LTH) under M . oryzae -infected or uninfected conditions; 636 were detected specifically upon M . oryzae infection. The circRNAs in IR25 were significantly more diverse than those in LTH, especially under M. oryzae infection. Particularly, the number of circRNAs generated per parent gene was much higher in IR25 than in LTH and increased in IR25 but decreased in LTH upon M. oryzae infection. The higher diversity of circRNAs in IR25 was further associated with more frequent 3′ and 5′ alternative back-splicing and usage of complex splice sites. Moreover, a subset of circRNAs was differentially responsive to M . oryzae in IR25 and LTH. We further confirmed that circR5g05160 promotes rice immunity against M . oryzae . Therefore, our data indicate that circRNA diversity is associated with different responses to M . oryzae infection in rice and provide a starting point to investigate a new layer of regulation in the rice- M . oryzae interaction.